BUSINESS DEVELOPMENT STRATEGY OF HONEY PINEAPPLE (Ananas comosus (L) Merr) PROCESSED PRODUCTS IN VITA NAS, BELIK DISTRICT, PEMALANG REGENCY - Amelia, Eka; Sasongko, Lutfi Aris; Wibowo, Hendri (Universitas Wahid Hasyim, 2021)
Honey Pineapple, one of the horticultural crops, can be made as a processed product. This research aims to analysis external internal factors, as well as to formulate alternative business development strategy of honey pineapple products in Vita Nas belik District, Pemalang Regency.Vita Nas has three types of products, namely pineapple syrup products, pineapple juice drinks and pineapple cocktails. Each product has different packaging. The data types used are primary and secondary. The method of data analysis is done by using IFE matrix, EFE matrix, IE matrix and SWOT matrix. The results of internal factors analysis (strength) include having a record of each sale, abundant raw materials, products have distinctive features, product diversification, the presence of training and the supply of labor skills, organizational structure is good and has adequate equipment. Internal factors (weakness) include the minimum use of websites and internet media, marketing area only in penday an its surrounding, the absence of sales marketing and a narrow packing place. External factors (opportunities) include cooperation with other entrepreneurs, the price stability of raw materials, have reular consumers and the support of local governments. External factors (threats) include rely on middle men, consumer preterences and the price is relatively expensive. Alternative strategies that can be done are: (1) strengthening cooperation between entrepreneurs and local governments, making the latest innovations with other entrepreneurs and developing product quality assurance; (2) Improve product promotion; (3) Establish direct cooperation with farmers, maintain product quality and provide the best service; (4) Improve promotional activities with websites and internet media. Keywords: Strategy, Processed, Honey Pineapple, SWOT.